Pro dan Kontra Mengenai Pengawasan Mahkamah Konstitusi oleh Komisi Yudisial - Kusuma, Anggita Febby; Rahma, Aura Mutia; Asyifa, Faradilla Kurnia; Devana, Kayla (Media Hukum Indonesia (MHI), 2024)
Supervision of Constitutional Court Judges by the Judicial Commission is part of efforts to ensure truth and justice through honor, dignity and behavior. In the Indonesian judicial system, the Judicial Commission can supervise Supreme Court Judges, but the Judicial Commission cannot supervise Constitutional Court Judges who are more independent because they have broader authority. In this supervision, the Judicial Commission acts as an independent balancing institution for judicial power so that judicial power can be accounted for and the public can see how well the judiciary is performing.